Nifaq Politik : Analisis Konseptual dalam Perspektif Al-Qur’an dan Hadis - Juanda Yusuf Siregar; Edi Hermanto; Ahmad Fachri Agustian; M. Firman Firdaus; Muhammad Farhan Rozi S (Jurnal Teologi Islam, 2026)
Political nifaq refers to a form of hypocrisy manifested in the exercise of power, characterized by a discrepancy between moral rhetoric and actual political conduct. In Muslim societies, political nifaq becomes a critical issue as religious symbols and discourse are often exploited to gain public legitimacy. This article aims to examine the concept of political nifaq from the perspectives of the Qur’an and the Prophetic traditions, as well as its implications for Islamic political ethics. This study employs a qualitative library research method with a normativetheological approach, utilizing the Qur’an, hadith, classical exegesis, and Islamic political thought literature as primary sources. The findings indicate that political nifaq constitutes an ethical deviation from Islamic political principles, leading to declining public trust, a crisis of leadership legitimacy, and moral degradation in political life. Therefore, Islam emphasizes honesty, trustworthiness, and consistency between words and actions as fundamental principles for establishing ethical and responsible political practices.